Development of an Empirical Model for the Wear Rate of Contact Bearing Materials Using a Standard Pin-On-Disc Test - Alhumaidah, Ahmad Abdullah; Alajmi, Hadyan Ali (Engineering International, 2018)
The wear rate for contact bearing materials is studied as a function of a number of potentially influential factors, including applied load, rotational speed, sliding distance, and material type. A standard pin-on-disc test is used to conduct this study. Two levels of applied load (20 and 10 N), rotational speed (100 and 200 rpm), sliding distance (150 and 450 m), and material type (AISI 440C and AISI 420 martensitic stainless steel) were tested. Tests is run according to the design of experiments (DOE) methodology. Experimental results are analysed based on the analysis of variance (ANOVA) approach in order to determine the factors that have a significant impact on the wear rate. An empirical model is developed to fit the true relationship between wear rate and the significant factors in the case AISI 440C and AISI 420 materials. Finally, the morphology of the worn surface is studied using SEM and EDX images.